To find which expression is equivalent to \( 9x^2 - 25 \), we can observe that \( 9x^2 - 25 \) fits the form of a difference of squares, which is given by the formula \( a^2 - b^2 = (a + b)(a - b) \).
In this case:
- \( a^2 = 9x^2 \) implies \( a = 3x \),
- \( b^2 = 25 \) implies \( b = 5 \).
Now, applying the difference of squares formula:
\[ 9x^2 - 25 = (3x)^2 - (5)^2 = (3x + 5)(3x - 5) \]
Thus, the expression equivalent to \( 9x^2 - 25 \) is:
\[ (3x + 5)(3x - 5) \]
So the correct response is:
(3x + 5)(3x - 5).